Comparison of body composition variables across a large sample of National Collegiate Athletic Association women athletes from 6 competitive sports - Fields, J. B.; Metoyer, C. J.; Casey, J. C.; Esco, M. R.; Jagim, A. R.; Jones, M. T. (The Journal of Strength and Conditioning Research, 2018)
Body composition (BC) plays a critical role in sport performance and athlete health. Body size and BC have been widely studied in men's sports, with reported changes observed over time. However, a paucity of current data exists in women athletes. The purpose of this descriptive study was to measure and compare BC data for collegiate women athletes from 6 competitive sports. A total of 524 athletes from 2 National Collegiate Athletic Association institutions participated: basketball (BB; n = 95), gymnastics (GYM; n = 42), lacrosse (LAX; n = 81), rowing (ROW; n = 57), soccer (SOC; n = 188), and volleyball (VB; n = 61). Body height (BH) and body mass (BM) were measured using a stadiometer and calibrated digital scale, respectively. Body fat percentage (BF%), fat mass (FM), and fat-free mass (FFM) were assessed using air displacement plethysmography. One-way analysis of variance was used to assess differences across sports. Least squares difference post hoc analyses were performed when a significant finding (p = 0.05) was identified. ROW had the highest BF% (29.9 ± 6.1%) and BB the greatest FFM (57.2 ± 6.1 kg). GYM had the lowest BM (58.9 ± 5.3 kg), FM (11.6 ± 2.6 kg), and BH (158.73 ± 2.13 cm). LAX, SOC, and VB had similar BF%. Body height was greatest for BB and VB (177.92 ± 7.55 cm, 176.79 ± 7.36 cm, respectively). These data may assist in the establishment of descriptive values for use in goal setting and exercise programming. The current data demonstrate a trend toward increased body size and BC from previous research.